Temperature Estimation in the Combustion Chamber of an Internal Combustion Engine. (15th July 2012) - Safakish, Gholam Reza
Abstract : The mathematical model of heat transfer phenomena is considered at the combustion chamber wall in an internal combustion (IC) engine. The mathematical model of proposed phenomena is established with respect to the crank angle. An inverse heat conduction problem is derived at the cylinder wall, and this problem is investigated numerically using Alifanov's regularization method. This problem studied as an optimization problem in which a squared residual functional is minimized with the conjugate gradient method. To show the ability of the proposed method, some test problems are considered.